Howard Cale papers - Cale, Howard, -1904.
Correspondence relating to Harrison's tour of New England and Montana and to family affairs. Correspondents include Mary Lord (Dimmick) Harrison, Charles W. Fairbanks, and Benjamin Harrison.
Lawyer of Indianapolis, Ind.; law firm partner of U.S. President Benjamin Harrison.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Fairbanks, Charles W. -- 1852-1918 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Harrison, Mary Lord, -- 1858-1948 -- Correspondence; Kale family; Montana -- Description and travel; New England -- Description and travel; Lawyers